Assessing regional integration in Africa IV : enhancing intra-African trade - United Nations; African Union; African Development Bank. (Addis Ababa : Economic Commission for Africa, 2010)
ARIA IV is a comprehensive empirical analysis of intra-African trade to determine why it has remained consistently low over the past decades. It also analyses the various policy issues and other factors that have affected intra-African trade, although these issues may have been addressed in different contexts.
Sales number: E.10.II.K.2"--T.p. verso.
Includes bibliographical references.
rua 30/10/13
Loans
Keywords: Africa; Regionalism; African cooperation; Economics; Business and politics; Social integration